2019
DOI: 10.1108/sampj-02-2018-0049
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the nexus between integrated reporting and sustainability embeddedness

Abstract: Purpose This paper aims to explore the nexus between integrated reporting and sustainability embeddedness. It seeks to contribute to a better understanding of the nexus by obtaining in-depth insight from the sensemaking of those in practice. Design/methodology/approach A single exploratory case study design strategy was applied to a leading stock exchange listed company in the property industry in South Africa. Rich qualitative data were gathered by applying multiple data gathering techniques to a diverse gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 50 publications
3
49
1
Order By: Relevance
“…In an attempt to address this problem, the IIRC developed an integrated reporting framework to guide companies on how to present, in a single integrated (IR), the financial and sustainability information in a way that provides better understanding of how a company creates value (IIRC, 2013;de Villiers et al, 2014;KPMG, 2017). 2 To-date, South Africa is the only country to mandate IR for listed companies (Barth et al, 2017), but IR has also gained traction, with the framework or aspects of it being embraced voluntarily by companies in over 70 other countries that include both developed countries (e.g., UK, Netherlands, Singapore, Japan, Australia) (see de Villiers et al, 2014;Le Roux and Pretorius, 2019) and developing countries (e.g., Kenya, Uganda, Mauritius, Nigeria, Zimbabwe) (see Bananuka et al, 2018;Modack, 2018;Injeni et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to address this problem, the IIRC developed an integrated reporting framework to guide companies on how to present, in a single integrated (IR), the financial and sustainability information in a way that provides better understanding of how a company creates value (IIRC, 2013;de Villiers et al, 2014;KPMG, 2017). 2 To-date, South Africa is the only country to mandate IR for listed companies (Barth et al, 2017), but IR has also gained traction, with the framework or aspects of it being embraced voluntarily by companies in over 70 other countries that include both developed countries (e.g., UK, Netherlands, Singapore, Japan, Australia) (see de Villiers et al, 2014;Le Roux and Pretorius, 2019) and developing countries (e.g., Kenya, Uganda, Mauritius, Nigeria, Zimbabwe) (see Bananuka et al, 2018;Modack, 2018;Injeni et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of environmental services (e.g., Jonker, 2007;Pettinotti et al, 2018) is a useful approach toward addressing the multiple stressors that lead to societal vulnerabilities in sub-Saharan Africa (Casale et al, 2010;Vogel et al, 2016;Falayi et al, 2019). Several studies have identified the correspondence between SDGs and aspects of the environment (sensu lato), including climate and ecosystems (e.g., Walmsley, 2002;Cumming et al, 2017;Nhamo, 2017;Omisore, 2018;Dawson et al, 2019) but this recognition has not followed through into meaningful developmental strategies that use environmental measures as performance indicators (Nhemachena et al, 2018;Le Roux and Pretorius, 2019;Jiménez-Aceituno et al, 2020). There is therefore a disconnection between the driving factors behind sustainable development, and the performance indicators used for monitoring achievement of SDGs (e.g., Patole, 2018;Schipper et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…the contents of sustainability reports (Adams, 2004; Adams et al , 1995; Adams and Kuasirikun, 2000; Bellringer et al , 2011; Boiral, 2013; Bouten et al , 2011; Busco et al , 2018; Deegan, 1996; Neu et al , 1998; Patten, 2002); and how sustainability reports are prepared (Farooq and De Villiers, 2019b; Herzig and Schaltegger, 2006; O’Dwyer, 2002; Owen, 2008) [5]. As the arrival of integrated reporting, researchers have begun to explore the determinants of integrated reporting (García-Sánchez et al , 2013; Jensen and Berg, 2012); the contents of integrated reports (Stacchezzini et al , 2016); barriers to the implementation of integrated reporting (Dumay et al , 2017); guidance on implementing integrated reporting (Abeysekera, 2013; Adams and Simnett, 2011); and how integrated reporting potentially drives integrated thinking, organisational change and sustainability embeddedness (Feng et al , 2017; Guthrie et al , 2017; Le Roux and Pretorius, 2019; Stubbs and Higgins, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there remains a need to adopt a holistic approach in existing sustainability scholarship (Morioka and de Carvalho, 2016). Similarly, academic efforts by Le Roux and Pretorius (2019 ) , Feng et al (2017 ) , Guthrie et al (2017 ) and Stubbs and Higgins (2014 ), on the how the side of integrated reporting, offer useful insights into the role played by integrated reporting in stimulating integrated thinking, organisational change and sustainability embeddedness. However, there remains a need for greater research examining the integration of sustainability into corporate practices (Le Roux and Pretorius, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation